2013
DOI: 10.1186/1756-8722-6-14
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of minimal residual disease (MRD) is useful to predict prognosis of adult patients with Ph-negative ALL: results of a prospective study (ALL MRD2002 Study)

Abstract: BackgroundAllogeneic hematopoietic stem cell transplantation (HSCT) for patients with Philadelphia chromosome (Ph)-negative acute lymphoblastic leukemia (ALL) in first complete remission (CR1) is much more intensive than multi-agent combined chemotherapy, although allogeneic HSCT is associated with increased morbidity and mortality when compared with such chemotherapy. Minimal residual disease (MRD) status has been proven to be a strong prognostic factor for adult patients with Ph-negative ALL.MethodsWe invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 36 publications
3
31
0
1
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21] They might thus be considered as a stratification tool, with the option to offer allogeneic SCT to patients with persistent molecular disease. 16,18,20,22 Conversely, novel genetic alterations originally described in children have also been reported to have an impact on the outcome of adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] They might thus be considered as a stratification tool, with the option to offer allogeneic SCT to patients with persistent molecular disease. 16,18,20,22 Conversely, novel genetic alterations originally described in children have also been reported to have an impact on the outcome of adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…164 Among the patients who achieved a CR after induction/consolidation (n = 39), those who were MRD negative (<0.1%) after induction had a significantly higher 3-year DFS (69% vs 31%; P=.004) compared with patients who were MRD positive; 3-year OS was higher among patients with MRD-negative status after induction, although the difference was not statistically significant (85% vs 59%). Based on multivariate Cox regression analysis, older age (>35 years) and MRD positivity after induction were significant independent factors predictive of decreased DFS.…”
Section: Mrd Assessment In Adult Allmentioning
confidence: 89%
“…WBC counts and MRD status after consolidation were not significant predictors of DFS outcomes. 164 Thus, MRD evaluation postinduction may provide additional risk stratification criteria among patients who would otherwise be considered standard risk according to traditional evaluation of prognostic factors.…”
Section: Mrd Assessment In Adult Allmentioning
confidence: 99%
“…This may highlight the molecular biology-based methods with a greater prognostic significance than conventional criteria for the detection of remission [24] [25]. Nagafuji et al [26] reported that chemotherapy should be continued as follow up therapy in ALL even with good prognosis in order to prevent leukemia relapse. However, patients with less favorable prognosis should be treated more aggressively.…”
Section: Discussionmentioning
confidence: 99%